2007
DOI: 10.1002/mrd.20732
|View full text |Cite
|
Sign up to set email alerts
|

Expression of αV and β3 integrin subunits during implantation in pig

Abstract: Integrin are adhesion molecules involved in uterine-conceptus interactions during the perimplantation period. In this study, the expression of alphaV and beta3 integrin subunits in endometrium during implantation in pigs was investigated. The immunohistochemical location was performed on paraformaldehyde-fixed, paraffin-embedded tissue sections, and the mRNA expression of alphaV was detected in endometrium. In addition, serum levels of estradiol, progesterone, follicle-stimulating hormone, and luteinizing horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
3
19
1
Order By: Relevance
“…and Johnson et al . reported a stromal decidualization-like response in the pregnant ovine and porcine uterus by studying osteopontin, integrin αV and β3 expression [29,30]. In our study, a similar phenomenon was found.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…and Johnson et al . reported a stromal decidualization-like response in the pregnant ovine and porcine uterus by studying osteopontin, integrin αV and β3 expression [29,30]. In our study, a similar phenomenon was found.…”
Section: Resultssupporting
confidence: 85%
“…Housekeeping gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was assayed as normalization control to correct for loading discrepancies for all samples assayed. Primer for GAPDH-1 was provided by BDBiosciences (Bedforld, USA); Primer for GAPDH-2 was used according to Lin et al [29]. They are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they found that the integrins expression may be used as a marker of endometrial receptivity and it is necessary for the proper embryo attachment during the implantation. Our observations were partially proved by Lin et al (2007). Using the pig as the model for the embryo attachment during the implantation, they showed the expression of alphaV and beta3 integrin in endometrium in all investigated stages of pig pregnancy (on Days 0, 12, 18, and 25 of pregnancy).…”
Section: Discussionsupporting
confidence: 60%
“…There is a considerable body of evidence that FAK is involved in integrin mediated signal transduction pathways (Cary and Guan, 1999; Hanks et al, 2003; Schaller, 2004; Playford et al, 2008) which correlates with the highly coordinated integrin expression in the endometrium (Aplin, 1997; Fazleabas et al, 1997; Lessey, 1997; Bowen and Hunt, 2000; Johnson et al, 2001; Lin et al, 2007; Srinivasan et al, 2009) and the blastocyst (Sutherland et al, 1993; Campbell et al, 1995; Schultz et al, 1997) in humans and other mammalian species at the time of implantation. Our laboratory has demonstrated a significant increase in integrin β3 expression along the apical plasma membrane of rat uterine luminal epithelial cells (Kaneko et al, 2011a) and in the trophoblast cells of the rat blastocyst (Kaneko et al, 2011b) at the time of implantation.…”
Section: Discussionmentioning
confidence: 99%